Classical Labor Values: Properties of Economic Reproduction. (1st October 2020) - Zachariah, David; Cockshott, Paul
Abstract : We consider economic value as a property that renders heterogeneous goods and services commensurable. Starting from the basic division of output between workers and non-workers, we are able to derive value as a property of systems of economic reproduction. We show its relation to value in classical political economy and in Sraffian economic theory. We go on to discuss the applicability of the derivation and its relevance for analyzing distribution, productivity and employment in a wide range of economies.